Identification of surface-basement layer distribution of Wangi-Wangi Island based on HVSR method of microtremor data - Rani Chahyani; Abdul Manan; Cindy Puspitafury; Kasmawati Kasmawati (Journal of Physics: Theories and Applications, 2020)
To find out the distribution of the surface-basement layer of Wangi-Wangi Island, it can be done by calculating the surface layer thickness of each measurement point using microtremor data. The surface layer thickness (h) also indicates the position of the basement to the surface. The microtremor recording data used in this study were 47 data. Furthermore, the data were processed using the HVSR method to obtained the soil predominant frequencies which together with the Vs30 values were used to calculated the h values. The results showed that the thickness of the surface layer or sediment layer of Wangi-Wangi Island was in the range of 5.7339 to 241.2557 meters. Based on its distribution, the areas with a thick surface layer are in the areas of Sombu, North Wandoka, Wandoka, South Wandoka, Pada Raya Makmur and Wanci. In the case of a disaster, these areas are thought to have the most potential to experience damage if an earthquake shakes.